THE IRANIAN EDUCATION AND ACADEMIC MOBILITY MODEL - AFZALI, Mehdi; RYAZANTSEV, Sergey; PISMENNAYA, Elena; ROSTOVSKAYA, Tamara (CENTRAL ASIA AND THE CAUCASUS, 2019)
The paper discusses the evolution of the educational model and trends of academic mobility in the Islamic Republic of Iran (IRI). It analyzes the sociodemographic structure of the population, the dynamics of the number of young people, as well as the dynamics and composition of the country’s school system. There is also an examination of the ways in which the process of emigration from Iran has evolved in the context of the country’s socio-political history in the 20th-21st centuries. Various levels of the Iranian education system are considered. The author examines the internationalization trends in higher education. The forms and trends of academic mobility, including exit and entry mobility, are delineated. In recent years, the visiting academic mobility of Iranian students has been targeted at the U.S., Turkey, Italy, Canada, and the UAE. There is a contemplation of the methods used for selecting Iranian students for studying abroad at the state budget’s expense, which is based on a system of state quotas and fairly high requirements for applicants. Iranian students studying abroad receive an academic scholarship. Those who receive such a scholarship must pay a deposit before being issued a final permit and commit to returning to Iran after graduation and working for up to six years. Recently, increasing the number of foreign students in Iran has become one of the priorities of the Ministry of Science, Research and Technology. The admission of foreign students has presently become one of the most important tasks undertaken by universities. One way to attract more foreign students and compete for them is to raise the status of universities and the country. Iran is growing more attractive as a recipient of international students from certain neighboring countries (Afghanistan, Iraq, Syria, Lebanon, Pakistan, and China). The role of academic mobility in the integration of Iran into the international educational and scientific space and the contribution of academic exchanges to the development of the national culture of Iran are emphasized.